Karakteristik Layanan Perpustakaan Perguruan Tinggi Dan Perpustakaan Daerah Kota Padang - Rahmah Aulia, Syakira; Madani, Serli (Departemen Informasi Perpustakaan dan Kearasipan, 2025)
Abstract This article aims to present a comprehensive overview of the services offered by three libraries in Padang city, namely Andalas University library, Padang State University library, and Padang City Regional library. From an analysis of the services available in each library service, this research seeks to identify the potential, challenges, functions of the library as well as opportunities for the development of service facilities in each of these libraries. This research aims to deeply understand the characteristics and needs of users in the three libraries. This research uses direct observation interview method on various aspects of services in Andalas University Library, Padang State University Library, and Padang City Regional Library. Observations showed variations in the availability and management of services in the three libraries, and identified a number of development potentials, operational and strategic challenges, unique functions of each library, and opportunities to improve service facilities. In-depth understanding of library users' characteristics and needs. It is hoped that these findings will contribute significantly to efforts to improve the quality and effectiveness of library services in Padang City, so that they can be more optimal in supporting the educational, research and literacy development needs of the community and students. Keywords: Library Service, College Library, Regional Library, Observation, service quality, information literacy.